PENGARUH LATIHAN SHUTTLE RUN TERHADAP KELINCAHAN FOOTWORK PERMAINAN BULUTANGKIS SISWA KELAS VIII SMP NEGERI 3 NANGA PINOH - Atmaja, Nur Moh Kusuma; Susilawati, Indria (STKIP Melawi, 2024)
Abstract: This study aims to determine the effect of shuttle run on increasing the agility of eighth grade students of SMP Negeri 3 Nanga Pinoh. This study is a pre-experiment, with samples not separate, because it cannot control all the variables that affect the results of the experiment. The design used in this study was